2004
DOI: 10.1038/sj.bmt.1704428
|View full text |Cite
|
Sign up to set email alerts
|

Failure of trilineage blood cell reconstitution after initial neutrophil engraftment in patients undergoing allogeneic hematopoietic cell transplantation – frequency and outcomes

Abstract: Summary:The outcomes of patients who experience the failure to reconstitute a trilineage of blood cells after initial neutrophil engraftment were evaluated in 178 patients with hematologic disorders, who underwent allogeneic HCT. Of 165 qualified patients (five with primary engraftment failure; eight deaths before day 60 of HCT), 43 (26%) satisfied the criteria for the initial (n ¼ 22; failure of platelet 420 000/ll or red blood cell transfusion independence/reticulocyte count X1.0% by day 60) or subsequent (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 18 publications
0
42
0
1
Order By: Relevance
“…Early reports found that the incidence of PGF ranged from 5 to 27 % [3,11]; however, there were a number of flaws with these studies, including a lack of distinction between PGF and graft rejection, as well as a lack of separation between cases of primary and secondary PGF. It is important to distinguish between these two types of PGF because we now realize that primary and secondary PGF are distinct entities with significantly different prognoses [4] and the majority of cases are actually secondary PGF.…”
Section: Discussionmentioning
confidence: 98%
“…Early reports found that the incidence of PGF ranged from 5 to 27 % [3,11]; however, there were a number of flaws with these studies, including a lack of distinction between PGF and graft rejection, as well as a lack of separation between cases of primary and secondary PGF. It is important to distinguish between these two types of PGF because we now realize that primary and secondary PGF are distinct entities with significantly different prognoses [4] and the majority of cases are actually secondary PGF.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, delayed hematopoietic recovery and related complications, including infection, anemia, and hemorrhage, occur in a considerable number of patients and seriously affect patient survival [1]. The reasons and mechanisms of delayed hematopoietic recovery are still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlymphoid cytopenia also frequently occurs after HSCT and has been described in the context of infections (e.g., cytomegalovirus), relapse and graft‐failure, or pharmacological induction . In particular, thrombocytopenia has been observed to associate with acute and chronic GvHD . Notably, in a multivariate analysis, acute GvHD was described as one of the factors that associated significantly with the secondary failure of platelet recovery (SFPR) .…”
Section: Introductionmentioning
confidence: 99%
“…This association was highlighted by the concomitant reversibility of thrombocytopenia and of clinical GvHD signs under immunosuppressive therapy . Furthermore, a low platelet count was proposed as an indicator of GvHD severity, and persistent thrombocytopenia has been described as an independent predictor of worse outcomes in patients with chronic and acute GvHD . Remarkably, patients with persistent thrombocytopenia do not die of hemorrhagic events, but rather other GvHD‐associated complications, particularly infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation